The genesis of perfection Adam and Eve in Jewish and Christian imagination - Anderson, Gary A. 1955- (Westminster John Knox Press, 2001)
This book explores both Jewish and Christian readings of the account of Adam and Eve and charts how human ends are configured by human beginnings.
Includes bibliographical references (p. 233-249) and indexes
Keywords: Adam <(Biblical figure)>; Eve <(Biblical figure)>; Adam und Eva; Bible. -- O.T. -- Genesis I-III -- Criticism, interpretation, etc. -- History; Bibel -- Genesis -- 1-3; Christendom; Jodendom; Christentum; Geschichte; Judentum; Sündenfall; Kirchenväter